Peran Advokat dalam Melindungi dan Mendampingi Tunawicara dalam Proses Hukum di Kantor Advokat Abdur Rohim S.H., M.Kn. dan Patners - jefri diantoro (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Speech-impaired persons represent a vulnerable group that faces communication barriers and the risk of discrimination within the judicial process. This research aims to analyze the role of advocates and the strategies for protecting the rights of speech-impaired persons in the judicial process at the Law Office of Abdur Rohim, S.H., M.Kn. and Partners. The method employed is empirical legal research with a socio-legal approach, utilizing interviews, observations and literature reviews. The findings indicate that advocates serve as legal assistants, communication mediators and protectors of human rights through the implementation of inclusive communication, the provision of reasonable accommodation and the reinforcement of procedural rights fulfillment. This role contributes to the realization of equal access to justice and supports a more inclusive judicial system for speech-impaired persons.